نظرية المعنى عند قدامة بن جعفر (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
تهدف هذه الدراسة إلى الوقوف على نظرية المعنى عند قدامة بن جعفر، وهي نظرية سبق أن تناولها الجاحظ من قبل، على أن هذه القضية عند قدامة ترتبط بنظرته إلى الشعر، فهو قول، موزون، مقفى، دال على معنى. وتتحدد مسألة الجودة فيه، أو الرداءة، من خلال علاقات ثنائية متبادلة بين هذه الأجزاء. ويصبح الشعر صناعة من الصناعات، ينظر إليها من زاوية الإجادة فيها. أمّا المعاني في الشعر فهي المادة الموضوعة، أو الهيولى، وتتحدد قيمتها من خلال الصورة التي تبرز فيها، ويشكل التناسب بين أجزاء الشعر بُعْداً من أبعاد هذه الصورة، وإذا كان المعنى ركناً رئيسياً من أركان الشعر فإن التناسب فيه يتحقق من خلال صحة التفسير، والتقسيم، والمقابلة، وهي مقولات منطقية سعى قدامة إلى تطبيقها على الشعر، وقد عول الباحث، للوصول إلى هذه النتائج، على شواهد نقدية مما قاله قدامة. This study aims at investigating the Theory of Meaning as presented by Qudaama Bin Ja’far, an Arab literary critic. Though previously investigated by Al-Jahith, Qudaama ties this theory. For Qudaama, poetry is a meaningful and rhyming form of language. He adds that the poetic quality (richness & poorness) is determined by a mutual and binary relation between meaning and rhyme. Poetry, according to Qudaama, is a craft evaluated according to quality criteria. Meaning in poetry, on the other hand, is determined via the image it conveys. Another point of relevance is the symmetry among parts of the poem. If meaning is one of the pillars of poetry, then symmetry is achieved through the accurate interpretation, evaluation, or comparison. Obviously, these are logical views that Qudaama tries to implement in poetry. Throughout the study, the researcher has relied on numerous pieces of concrete evidence of what Qudaama and other philosophers had previously claimed.